### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

norm(nil) → 0
norm(g(x, y)) → s(norm(x))
f(x, nil) → g(nil, x)
f(x, g(y, z)) → g(f(x, y), z)
rem(nil, y) → nil
rem(g(x, y), 0) → g(x, y)
rem(g(x, y), s(z)) → rem(x, z)

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
norm(g(x, y)) →+ s(norm(x))
gives rise to a decreasing loop by considering the right hand sides subterm at position [0].
The pumping substitution is [x / g(x, y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

norm(nil) → 0'
norm(g(x, y)) → s(norm(x))
f(x, nil) → g(nil, x)
f(x, g(y, z)) → g(f(x, y), z)
rem(nil, y) → nil
rem(g(x, y), 0') → g(x, y)
rem(g(x, y), s(z)) → rem(x, z)

S is empty.
Rewrite Strategy: FULL

### (5) SlicingProof (LOWER BOUND(ID) transformation)

Sliced the following arguments:
g/1
f/0

### (6) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

S is empty.
Rewrite Strategy: FULL

Infered types.

### (8) Obligation:

TRS:
Rules:
norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

Types:
norm :: nil:g → 0':s
nil :: nil:g
0' :: 0':s
g :: nil:g → nil:g
s :: 0':s → 0':s
f :: nil:g → nil:g
rem :: nil:g → 0':s → nil:g
hole_0':s1_0 :: 0':s
hole_nil:g2_0 :: nil:g
gen_0':s3_0 :: Nat → 0':s
gen_nil:g4_0 :: Nat → nil:g

### (9) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
norm, f, rem

### (10) Obligation:

TRS:
Rules:
norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

Types:
norm :: nil:g → 0':s
nil :: nil:g
0' :: 0':s
g :: nil:g → nil:g
s :: 0':s → 0':s
f :: nil:g → nil:g
rem :: nil:g → 0':s → nil:g
hole_0':s1_0 :: 0':s
hole_nil:g2_0 :: nil:g
gen_0':s3_0 :: Nat → 0':s
gen_nil:g4_0 :: Nat → nil:g

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))
gen_nil:g4_0(0) ⇔ nil
gen_nil:g4_0(+(x, 1)) ⇔ g(gen_nil:g4_0(x))

The following defined symbols remain to be analysed:
norm, f, rem

### (11) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)

Induction Base:
norm(gen_nil:g4_0(0)) →RΩ(1)
0'

Induction Step:
norm(gen_nil:g4_0(+(n6_0, 1))) →RΩ(1)
s(norm(gen_nil:g4_0(n6_0))) →IH
s(gen_0':s3_0(c7_0))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (13) Obligation:

TRS:
Rules:
norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

Types:
norm :: nil:g → 0':s
nil :: nil:g
0' :: 0':s
g :: nil:g → nil:g
s :: 0':s → 0':s
f :: nil:g → nil:g
rem :: nil:g → 0':s → nil:g
hole_0':s1_0 :: 0':s
hole_nil:g2_0 :: nil:g
gen_0':s3_0 :: Nat → 0':s
gen_nil:g4_0 :: Nat → nil:g

Lemmas:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))
gen_nil:g4_0(0) ⇔ nil
gen_nil:g4_0(+(x, 1)) ⇔ g(gen_nil:g4_0(x))

The following defined symbols remain to be analysed:
f, rem

### (14) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
f(gen_nil:g4_0(n188_0)) → gen_nil:g4_0(+(1, n188_0)), rt ∈ Ω(1 + n1880)

Induction Base:
f(gen_nil:g4_0(0)) →RΩ(1)
g(nil)

Induction Step:
f(gen_nil:g4_0(+(n188_0, 1))) →RΩ(1)
g(f(gen_nil:g4_0(n188_0))) →IH
g(gen_nil:g4_0(+(1, c189_0)))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (16) Obligation:

TRS:
Rules:
norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

Types:
norm :: nil:g → 0':s
nil :: nil:g
0' :: 0':s
g :: nil:g → nil:g
s :: 0':s → 0':s
f :: nil:g → nil:g
rem :: nil:g → 0':s → nil:g
hole_0':s1_0 :: 0':s
hole_nil:g2_0 :: nil:g
gen_0':s3_0 :: Nat → 0':s
gen_nil:g4_0 :: Nat → nil:g

Lemmas:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)
f(gen_nil:g4_0(n188_0)) → gen_nil:g4_0(+(1, n188_0)), rt ∈ Ω(1 + n1880)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))
gen_nil:g4_0(0) ⇔ nil
gen_nil:g4_0(+(x, 1)) ⇔ g(gen_nil:g4_0(x))

The following defined symbols remain to be analysed:
rem

### (17) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
rem(gen_nil:g4_0(n424_0), gen_0':s3_0(n424_0)) → gen_nil:g4_0(0), rt ∈ Ω(1 + n4240)

Induction Base:
rem(gen_nil:g4_0(0), gen_0':s3_0(0)) →RΩ(1)
nil

Induction Step:
rem(gen_nil:g4_0(+(n424_0, 1)), gen_0':s3_0(+(n424_0, 1))) →RΩ(1)
rem(gen_nil:g4_0(n424_0), gen_0':s3_0(n424_0)) →IH
gen_nil:g4_0(0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (19) Obligation:

TRS:
Rules:
norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

Types:
norm :: nil:g → 0':s
nil :: nil:g
0' :: 0':s
g :: nil:g → nil:g
s :: 0':s → 0':s
f :: nil:g → nil:g
rem :: nil:g → 0':s → nil:g
hole_0':s1_0 :: 0':s
hole_nil:g2_0 :: nil:g
gen_0':s3_0 :: Nat → 0':s
gen_nil:g4_0 :: Nat → nil:g

Lemmas:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)
f(gen_nil:g4_0(n188_0)) → gen_nil:g4_0(+(1, n188_0)), rt ∈ Ω(1 + n1880)
rem(gen_nil:g4_0(n424_0), gen_0':s3_0(n424_0)) → gen_nil:g4_0(0), rt ∈ Ω(1 + n4240)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))
gen_nil:g4_0(0) ⇔ nil
gen_nil:g4_0(+(x, 1)) ⇔ g(gen_nil:g4_0(x))

No more defined symbols left to analyse.

### (20) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)

### (22) Obligation:

TRS:
Rules:
norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

Types:
norm :: nil:g → 0':s
nil :: nil:g
0' :: 0':s
g :: nil:g → nil:g
s :: 0':s → 0':s
f :: nil:g → nil:g
rem :: nil:g → 0':s → nil:g
hole_0':s1_0 :: 0':s
hole_nil:g2_0 :: nil:g
gen_0':s3_0 :: Nat → 0':s
gen_nil:g4_0 :: Nat → nil:g

Lemmas:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)
f(gen_nil:g4_0(n188_0)) → gen_nil:g4_0(+(1, n188_0)), rt ∈ Ω(1 + n1880)
rem(gen_nil:g4_0(n424_0), gen_0':s3_0(n424_0)) → gen_nil:g4_0(0), rt ∈ Ω(1 + n4240)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))
gen_nil:g4_0(0) ⇔ nil
gen_nil:g4_0(+(x, 1)) ⇔ g(gen_nil:g4_0(x))

No more defined symbols left to analyse.

### (23) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)

### (25) Obligation:

TRS:
Rules:
norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

Types:
norm :: nil:g → 0':s
nil :: nil:g
0' :: 0':s
g :: nil:g → nil:g
s :: 0':s → 0':s
f :: nil:g → nil:g
rem :: nil:g → 0':s → nil:g
hole_0':s1_0 :: 0':s
hole_nil:g2_0 :: nil:g
gen_0':s3_0 :: Nat → 0':s
gen_nil:g4_0 :: Nat → nil:g

Lemmas:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)
f(gen_nil:g4_0(n188_0)) → gen_nil:g4_0(+(1, n188_0)), rt ∈ Ω(1 + n1880)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))
gen_nil:g4_0(0) ⇔ nil
gen_nil:g4_0(+(x, 1)) ⇔ g(gen_nil:g4_0(x))

No more defined symbols left to analyse.

### (26) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)

### (28) Obligation:

TRS:
Rules:
norm(nil) → 0'
norm(g(x)) → s(norm(x))
f(nil) → g(nil)
f(g(y)) → g(f(y))
rem(nil, y) → nil
rem(g(x), 0') → g(x)
rem(g(x), s(z)) → rem(x, z)

Types:
norm :: nil:g → 0':s
nil :: nil:g
0' :: 0':s
g :: nil:g → nil:g
s :: 0':s → 0':s
f :: nil:g → nil:g
rem :: nil:g → 0':s → nil:g
hole_0':s1_0 :: 0':s
hole_nil:g2_0 :: nil:g
gen_0':s3_0 :: Nat → 0':s
gen_nil:g4_0 :: Nat → nil:g

Lemmas:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))
gen_nil:g4_0(0) ⇔ nil
gen_nil:g4_0(+(x, 1)) ⇔ g(gen_nil:g4_0(x))

No more defined symbols left to analyse.

### (29) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
norm(gen_nil:g4_0(n6_0)) → gen_0':s3_0(n6_0), rt ∈ Ω(1 + n60)